How quasi-internal resources enhance firm performance during large-scale emergencies: The role of trade-off between CSR and business innovations - He, X.; Lopes da Costa, R.; Ni, D.; Han, W. (Sustainability, 2024)
Although quasi-internal resources—such as strategic alliances, long-term partnerships, and collaborative networks—typically enhance a firm’s adaptability, their effectiveness can be compromised in crisis situations due to supply chain disruptions, strained partnerships, and volatile market conditions. This research explores how quasi-internal resources influence firm performance through the trade-off between corporate social responsibility (CSR) and business innovation, with a particular focus on the moderating role of market environmental uncertainty. We developed a theoretical model grounded in resource dependence theory and tested our hypotheses using PLS-SEM analysis on data from 397 valid questionnaires collected from various companies. The findings reveal that quasi-internal resources do not directly enhance firm performance during large-scale emergencies. However, they play a critical role in strengthening the trade-off between CSR and business innovation, particularly through strategic adjustments and decision-making processes, which mediate their impact on performance. Conversely, the trade-off in incentive mechanisms does not significantly mediate this relationship. Additionally, market environmental uncertainty positively moderates the relationship between quasi-internal resources and the trade-offs in incentive mechanisms and decision-making processes, but it does not significantly affect strategic adjustments. These insights underscore the importance of strategic resource management in sustaining firm performance amidst uncertainty.